دور السياسة النقدية و المالية في معالجة التضخم في الجزائر خلال الفترة (2010-2020) - شكري, معلول; أحمد الرفاعي, شويرف (جامعة الوادي - University of Eloued, 2023)
"تهدف هذه الدراسة الى إبراز دور السياسة النقدية والمالية في الجزائر خلال الفترة الممتدة من (2010-2020) من خلال جمع المعطيات و الإحصائيات المالية للوضع الاقتصادي و السوق النقدي في الجزائر خلال هذه الفترة و إعطاء تحليل و أسباب لكل ظاهرة للخروج بتشخيص نهائي يجيب على الإشكالية المطروحة في هذه الدراسة و المتمثلة في : مامدى فعالية السياسة النقدية و السياسة المالية في معالجة التضخم في الجزائر خلال الفترة الممتدة من 2010 إلى غاية 2020 ؟ حيث تم التطرق إلى إجراءات السياسة النقدية و السياسة المالية في الجزائر خلال فترة الدراسة وكيفية تفاعلها و معالجتها للأوضاع الاقتصادية التي مست البلاد و نتائج هاته الإجراءات ، حيث خلصت هذه الدراسة إلى أن التنسيق بين السياستين يجعل منهما أكثر فاعلية من اجل إعادة حالة الاستقرار للوضع الاقتصادي ، ففي حالة التضخم تقوم السلطات النقدية بالتدخل عن طريق استخدام أدواتها للخفض من حجم المعروض النقدي من اجل التخفيف من حدة التضخم و منه فعلى السلطات المالية أن تتعاون مع هذه السياسة و تتجنب الإجراءات المضادة ،مثل العمل على زيادة النفقات أو خفض الضرائب وإنما إتباع سياسة مالية انكماشية تتماشى مع أهداف السياسة النقدية و العكس صحيح ؛ كما يجب إعطاء أهمية أكبر للسياسة النقدية من خلال الاستقلالية المطلقة لبنك الجزائر ، و العمل على ضبط المالية العامة من خلال تحصيل الإيرادات وتطوير السياسة الضريبية ومحاربة التهرب الضريبي، والخفض من الإنفاق العام و توجيهه نحو المشاريع الاستثمارية و ترشيد الإنفاق الاستهلاكي، و مراجعة وهيكلة سياسة الدعم. ""This study aims to highlight the role of monetary and fiscal policy in Algeria during the period 2010-2020 through the collection of financial data and statistics on the economic situation and the monetary market in Algeria during this period and to give an analysis and reasons for each phenomenon to come up with a final diagnosis that answers the problem raised in this study, namely: How effective is monetary and fiscal policy in addressing Algeria's inflation from 2010 to 2020?؛ The procedures of monetary and fiscal policy in Algeria were discussed during the study period and how they interact and address the economic conditions affecting the country and the results thereof. The study concluded that coordination between the two policies makes them more effective in order to restore stability to the economic situation, In the case of inflation, monetary authorities intervene by using their instruments to reduce the volume of the money supply in order to mitigate inflation and from it. The financial authorities must cooperate with this policy and avoid countermeasures. fiscal policy in line with monetary policy objectives and vice versa; Monetary policy must also be given greater importance through the Bank of Algeria's absolute autonomy, the control of public finances through revenue collection, the development of tax policy, the fight against tax evasion, the reduction of public spending and its orientation towards investment projects, the rationalization of consumer spending, and the review and structuring of support policy. "
Keywords: السياسة النقدية ،السياسة المالية، التضخم; monetary policy, financial policy, inflation